Rooftop Solar Policy and Metropolitan Governance: Paradiplomacy as a Policy Channel in Five Southeast Asian Cities - Krisnadi, Muhammad Faiz (Journal of Paradiplomacy and City Networks, 2026)
ASEAN cities face mounting pressure to expand rooftop solar deployment, yet adoption remains uneven across the region. While previous studies have emphasized national renewable energy policies, less attention has been given to how city-level policy instruments and paradiplomacy shape local photovoltaic uptake. This article examines rooftop solar instruments across five Southeast Asian metropolitan governments: Singapore, Jakarta, Kuala Lumpur, Ho Chi Minh City, and Bangkok. Using comparative case evidence and an exploratory city-year panel for 2010–2024, the analysis distinguishes national policies from city-level regulatory instruments. The findings reveal heterogeneous policy effects. Singapore demonstrates the strongest procurement-led expansion, whereas Kuala Lumpur and Bangkok remain at earlier implementation stages. Jakarta and Ho Chi Minh City illustrate the difficulty of separating national incentives from local initiatives. The evidence further suggests that paradiplomacy serves not merely as symbolic international engagement but as a practical policy mechanism through which city networks, donor partnerships, and technical learning strengthen local implementation capacity. The article argues that ASEAN's urban energy transition depends not only on national incentives but also on the regulatory, institutional, and diplomatic capacity of metropolitan governments to translate climate commitments into effective rooftop solar programmes.